Introduction to Lean. (O'Reilly Media, Inc., 2018)
If you've seen multiple products fail in the market, been asked to work on a project that might be doomed, or have a product idea--but aren't sure how to start to make it a reality--it's probably time to master Lean, the concept successful startups are nailing and larger organizations are beginning to catch on to. With this training, you'll first explore how the Lean approach grew from challenges with traditional waterfall and agile methods. Then, you'll discover how to make informed decisions on your own projects by using Build-Measure-Learn cycles. By hearing real world examples that describe how Lean fits into typical work contexts, you'll learn to identify scenarios that can benefit from this approach and gain the ability to answer questions about the Lean process, so your teams can avoid product failure and realize value sooner. Understand the differences between a Lean approach and the Waterfall and Agile methodologies Learn why people are talking about Lean and how it helps them in their daily product roles Discover the importance of failing fast and what that means Gain a solid understanding of the Lean approach to product development Kylie Castellaw (Lead Design & Product Consultant) and Maryam Aidini (Senior Consultant) are Lean coaches who both work for Thoughtworks. Kylie comes to the Lean practice with a background as a UX designer/researcher and cognitive psychologist. She holds degrees in graphics design and human factors psychology. Maryam Aidini started her career as a software engineer and has many years of experience delivering software products using Agile and Lean. Maryam holds degrees in software engineering and advanced computing.